POLA TATA HUBUNGAN KERJA DALAM PEMBANGUNAN HUTAN KEMASYARAKATAN - Epi Syahadat; Elvida Yosefi Suryandari (Jurnal Analisis Kebijakan Kehutanan, 2016)
Community empowerment is one of important element in sustainable forest management. One of causes of degraded forest resources in Indonesia is unplanned empowerment program by the Government. One of local community empowerment program is the community based forest (CBF) that are supported by the Forestry Minister Decree No. P.37/2007 jo P.18 /2009 jo P.13/2010 jo P.52/2011 jo P.88/2014. This regulation could be used as an operational implementation of CBF. The aim of this study are to (a) identify all para pihaks involved in CBF, (b) review roles, functions and contribution from each para pihak in CBF development. The objectives of this study are (a) available information on CBF para pihaks; (b) available information on roles, functions and contribution from each para pihak. The study results showed that: a) the organizational structure implementation CBF central agencies have a role in preparing work plans and monitoring of environmental impacts, and district government responsible for the implementation of CBF activities; b) the role of government is very strongly associated with the provision of recommendations forest areas clean and clear which will be the area of conditional land development, and assistance with community.